Radiological Investigation of Gas Embolism in the East Asian Finless Porpoise (Neophocaena asiaeorientalis sunameri) - Adams Hei Long Yuen; Sang Wha Kim; Sung Bin Lee; Seyoung Lee; Young Ran Lee; Sun Min Kim; Cherry Tsz Ching Poon; Jun Kwon; Won Joon Jung; Sib Sankar Giri; Sang Guen Kim; Jeong Woo Kang; et al. (Frontiers in Marine Science, 2022)
Cetaceans have long been considered biologically adapted to suffer no adverse effects from diving-related tissue gas tension. However, increasing reports of gas embolism in cetaceans inhabiting European, Mediterranean and American waters have challenged the conventional understanding of marine mammal diving physiology. In human hyperbaric medicine, virtopsy techniques such as post-mortem computed tomography (PMCT) facilitate the visualization of gas embolism and could be performed adjunct to conventional autopsy. This research presents the first case of gas embolism identified in an East Asian finless porpoise inhabiting Asian waters. Massive gas embolic lesions were found in the liver, which had been compressing both the lungs and abdominal organs, and signs of pneumonia and parasitic infection were observed in both lungs. It is hypothesized that this porpoise might have been unable to expel in vivo gas bubbles from its circulation due to pulmonary dysfunction. Consequently, gas bubbles agglomerated in the liver, resulting in the development of gas embolic lesions. The findings of the present study provide insights into the occurrence of gas embolism in the East Asian finless porpoise, highlighting the potential of PMCT as a promising tool for the diagnosis of gas embolism in stranded cetaceans.